2023
DOI: 10.3847/2041-8213/acaf67
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Circular Polarimetry of the Optically Bright Relativistic Tidal Disruption Event AT 2022cmc

Abstract: Tidal disruption events (TDEs) occur when a star orbiting a massive black hole is sufficiently close to being tidally ripped apart by the black hole. AT 2022cmc is the first relativistic TDE that was observed (and discovered) as an optically bright and fast transient, showing signatures of nonthermal radiation induced by a jet that is oriented toward the Earth. In this work, we present optical linear and circular polarization measurements, observed with the Very Large Telescope/FORS2 in the R band (which corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Eight free parameters are considered in the fitting, i.e., the isotropic kinetic energy E K,iso , the initial lorentz factor Γ 0 of the jet, the jet opening angle θ j , the CNM profile parameter k, the number density of the CNM medium n 18 at R = 10 18 cm, the electron distribution power-law index p, and the energy fraction in electrons ò e and in magnetic field ò B . The viewing angle θ obs is fixed to 0°in the fit due to the on-axis jet as suggested by Andreoni et al (2022) and Pasham et al (2023), and also by the nearly zero observed polarization degrees (Cikota et al 2023).…”
Section: Constraining the Cnm Profile With Fs Model Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight free parameters are considered in the fitting, i.e., the isotropic kinetic energy E K,iso , the initial lorentz factor Γ 0 of the jet, the jet opening angle θ j , the CNM profile parameter k, the number density of the CNM medium n 18 at R = 10 18 cm, the electron distribution power-law index p, and the energy fraction in electrons ò e and in magnetic field ò B . The viewing angle θ obs is fixed to 0°in the fit due to the on-axis jet as suggested by Andreoni et al (2022) and Pasham et al (2023), and also by the nearly zero observed polarization degrees (Cikota et al 2023).…”
Section: Constraining the Cnm Profile With Fs Model Fitmentioning
confidence: 99%
“…The low polarization (consistent with zero) favors the jet with low magnetic field energy density (Cikota et al 2023). We therefore use a relatively smaller value of the lower limit for ò B .…”
Section: Constraining the Cnm Profile With Fs Model Fitmentioning
confidence: 99%